Exploration and thinking of container technology for telecom operators - Gang LU; Xinzhang YANG; Zhenwei HE; Ling ZHANG; Liyun YAN (Dianxin kexue)
Container is an operating environment which has relatively isolated resources running on top of the operating system kernel，and the development of container technology corresponds to the essential requirements of cloud computing.As a senior player in cloud computing field，the telecom operators must pay more attention to container technology.The technology background of container was briefly introduced，the potential application scenarios for telecom operators were analyzed，the preliminary exploratory cases for telecom operators were summarized，and the possible positive role of container technology in transformation and upgrade for telecom operators was discussed.